The effect of perceived social support, from friends and family, on the wellbeing of immigrant adolescents in Iceland - Kristín Ásta Lárusdóttir 1999- (2021)
Previous research has found that social support from family and friends has a positive impact on the wellbeing of immigrant children and adolescents. Lack of social support from family and friends can negatively affect mental health, such as increased anxiety and depressive symptoms and decreased capacity to handle stress. Previous research also found that language proficiency was positively correlated with immigrant’s wellbeing, as increased language proficiency led to more successful social interactions. The data used came from a recent questionnaire by ICSRA Icelandic Center for Social Research and Analysis sent to colleges in Iceland. The participants were 2049 adolescents ages 15 to 20 years old in Iceland, of which 317 individuals had an immigrant background. An independent sample T-test showed that adolescents with an immigrant background had a lower mean life satisfaction than those with no immigrant background. Additionally, adolescents with an immigrant background perceived less social support from friends and family than adolescents with no immigrant background. There is very little research on the wellbeing of children and adolescents with an immigrant background in Iceland. These results highlight the need for more research on why these young individuals perceive less social support from friends and family and how to improve their wellbeing. Niðurstöður fyrri rannsókna sýna að félagslegur stuðningur frá fjölskyldu og vinum hefur jákvæð áhrif á vellíðan barna og ungmenna með erlendan bakgrunn. Vöntun á félagslegum stuðningi frá fjölskyldu og vinum getur haft neikvæð áhrif á geðheilsu, svo sem aukið kvíða og þunglyndiseinkenni, og dregið úr getu til að bregðast við áreiti og stressi. Fyrri rannsóknir hafa líka sýnt fram á að jákvæð tengsl eru á milli tungumálakunnáttu og vellíðan innflytjenda, þar sem aukin tungumálakunnátta leiddi til árangursríkra félagslegra samskipta. Gögnin sem notuð voru í rannsókninni eru fengin úr nýlegum spurningalista sem Rannsóknir og Greining sendi á alla menntaskóla á ...